Radiometric survey in geological mapping of parts of basement complex area of Nigeria - O., Ademila; S., Akingboye A.; I., Ojamomi A. (Vietnam Journal of Earth Sciences, 2018)
Radiometric methods were used to investigate the radioactive properties of rocks in parts of southwestern Nigeria with a view to interpreting the geological structure and abundance of natural radioactive elements in the main type rocks. The airborne radiometric dataset of Ikole Sheet and ground radiometric data recorded from eight traverses in Akoko axis of the study area were processed. Results presented as maps and profiles displayed variations of high and low radioactive concentrations across the area. These maps showed moderate to very high concentrations and very low to low concentrations of the radioelements; uranium (4.5-13.0 ppm); (LLD-low limit of detection -3.0 ppm), Th (25.0-70.0 ppm); (8.5-16.0 ppm) and K (2.0-4.0 %); but the most often observed values are in the range 2.5-7.0 ppm, 22.0-30.0 ppm and 3.0-4.0% for U, Th, and K respectively. High concentrations imply that the rocks are crystalline, undeformed and are rich in feldspar and U-Th bearing minerals. While low radioactivity is attributed to varying geologic framework compositions; weathered materials or fluids formed as a result of intense metamorphism. The radiometric datasets proved valuable in delineating different rock types and serve as a complementary tool in identifying geochemical zoning of rocks in the area. References Ajibade A.C. and Fitches W.R., 1988. The Nigerian Precambrian and the Pan-African Orogeny, Precambrian Geology of Nigeria, 45-53. Ajibade A.C., Woakes M. and Rahaman M.A., 1987.Proterozoic crustal development in Pan-African regime of Nigeria: In A. Croner (ed.) Proterozoic Lithospheric Evolution Geodynamics, 17, 259-231. Appleton J.D., Miles J.C.H., Green B.M.R, Larmour R., 2008. Pilot study of the application of Tellus airborne radiometric and soil geochemical data for radon mapping. Journal of Environmental Radioactivity, 99, 1687-1697. Arisekola T.M. and Ajenipa R.A., 2013. Geophysical data results preliminary application to uranium and thorium exploration. IAEA-CYTED-UNECE Workshop on UNFC-2009 at Santiago, Chile 9-12, July, 12. Bayowa O.G., Olorunfemi O.M., Akinluyi O.F. and Ademilua O.L., 2014.A Preliminary Approach to Groundwater Potential Appraisal of Ekiti State, Southwestern Nigeria. International Journal of Science and Technology (IJST), 4(3), 48-58. Bierwirth P.N., 1997. The use of airborne gamma-emission data for detecting soil properties.Proceedings of the Third International Airborne Remote Sensing Conference and Exhibition.Copenhagen, Denmark. Grasty R.L. and Multala J., 1991. A correlation technique for separating natural and man-made airborne gamma-ray spectra. In: Current Research, Part D, Geological Survey of Canada, 111-116. Grasty R.L., Minty B.R.S., 1995a. A guide to the technical specifications for airborne gamma ray surveys. Australian Geological Survey Organization, Record. Grasty R.L., Minty B.R.S., 1995b. The standardization of airborne gamma-ray surveys in Australia. Exploration Geophysics, 26, 276-283. IAEA, 1991. Airborne gamma ray spectrometer surveying, International Atomic Energy Agency, Technical Report Series, 323. IAEA, 2007.International Atomic Energy Agency. Safety Glossary, Terminology used in Nuclear Safety and Radiation Protection-2007 Edition. Jones H.A. and Hockey, 1964.The Geology of part of’ Southwestern Nigeria.Geological Survey, Nigeria bulletin, 31. Kearey P., Brooks M. and Hill I., 2002. An Introduction to Geophysical Exploration.3rd ed. Oxford: Blackwell Science, 262. Milsom J., 2003. Field Geophysics: The geological field guide series, John Milsom University College, London. Published by John Wiley and Sons Ltd. Third edition, 51-70. MontajTM Tutorial, 2004. Two - Dimensional frequency domain processing of potential field data. Nigeria Geological Survey Agency (NGSA), 2009. Geological map of Nigeria prepared by Nigeria Geological Survey Agency, 31, ShetimaMangono Crescent Utako District, Garki, Abuja, Nigeria. Omosanya K.O., Ariyo S.O., Kaigama U., Mosuro G.O., and Laniyan T.A., 2015. An outcrop evidence for polycyclic orogenies in the basement complex of Southwestern Nigeria. Journal of Geography and Geology, 7(3), 24-34. Oyawoye, M.O., 1972. The Basement Complex of Nigeria.In African Geology. T.F.J. Dessauvagie and A.J. Whiteman (Eds) Ibadan University Press, 67-99. Oyinloye A.O., 2011. Geology and Geotectonic Setting of the Basement Complex Rocks in Southwestern Nigeria: Implications on Provenance and Evolution. Earth and Environmental Sciences, 98-117. ISBN: 978-953-307-468-9. Rahaman M.A., 1981. Recent Advances in the Study of the Basement Complex of Nigeria.First Symposium on the Precambrian Geology of Nigeria, Summary. Rahaman M.A., Emofureta W.O. and Vachette M., 1983. The potassic-grades of the Igbeti area: Further evaluation of the polycyclic evolution of the Pan-African Belt in South-western Nigeria. Precambrian Resources, 22, 75-92. Woakes M., Rahaman M.A., Ajibade A.C., 1987. Some Metallogenetic Features of the Nigerian Basement. Journal of African Earth Sciences, 6(5), 655-664.